Antiproliferative and structure activity relationships of amaryllidaceae alkaloids - Cedrón, Juan C. (2015)
The antiproliferative activity of a set of seven natural Amaryllidaceae alkaloids and 32 derivatives against four cancer cell lines (A2780, SW1573, T47-D and WiDr) was determined. The best antiproliferative activities were achieved with alkaloids derived from pancracine (2), haemanthamine (6) and haemantidine (7). For each skeleton, some structure-activity relationships were outlined.